Novel Antibacterial Class - Dandliker, Peter J. (American Society for Microbiology, 2003)
We report the discovery and characterization of a novel ribosome inhibitor (NRI) class that exhibits selective and broad-spectrum antibacterial activity. Compounds in this class inhibit growth of many gram-positive and gram-negative bacteria, including the common respiratory pathogens Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, and Moraxella catarrhalis, and are nontoxic to human cell lines. The first NRI was discovered in a high-throughput screen designed to identify inhibitors of cell-free translation in extracts from S. pneumoniae. The chemical structure of the NRI class is related to antibacterial quinolones, but, interestingly, the differences in structure are sufficient to completely alter the biochemical and intracellular mechanisms of action. Expression array studies and analysis of NRI-resistant mutants confirm this difference in intracellular mechanism and provide evidence that the NRIs inhibit bacterial protein synthesis by inhibiting ribosomes. Furthermore, compounds in the NRI series appear to inhibit bacterial ribosomes by a new mechanism, because NRI-resistant strains are not cross-resistant to other ribosome inhibitors, such as macrolides, chloramphenicol, tetracycline, aminoglycosides, or oxazolidinones. The NRIs are a promising new antibacterial class with activity against all major drug-resistant respiratory pathogens.